A comparative study on the training program for sales personnel in selected apparel retail stores in Metro Manila - Malabad, Anne Lorraine Abarca
Retailing is the business of selling products and services to the final consumer. Having the most customer contact, it is important that its people give quality service through product knowledge and good customer relations. Training helps sales personnel develop their expert abilities (Troxell & Stone, 1981). The objective of the research is to compare the training programs of ten apparel retail stores. Specifically it aimed to determine the training methods, types of training and the training contents given to sales personnel. Define the expected competencies of sales personnel and determine the training given to salespersons related to the store's merchandise. The research also takes into consideration how retail stores used the job description and qualifications of salespersons as well as the store's level of service in their training program. Descriptive research using survey method was used in gathering data. Likewise, descriptive statistical techniques were utilized to analyze and summarize the data gathered. Two sets of questionnaires were provided to ten apparel retail stores located in SM City North Edsa, Quezon City, all of them responded. The research provides baseline information on how apparel retail companies hone the selling skills, management capability and merchandising skills of their sales personnel. It provides information on the training program of the different stores for their salespersons. The research also gives information to BSCT graduates and students on what aspect of the Clothing Technology program is incorporated in the training program of salespersons. Analysis of data revealed that apparel retail stores used the three types of training with on-the-job training the most frequently used. Generally, the companies utilized demonstration method giving high emphasis on customer service. Good human relations, promptness in attending to customers and good manners topped in the ranking of required competencies of sales personnel. The study found out that the ten apparel retail stores have similarity in their training program. They have the same expected competencies of sales personnel, used the same training types and method and cover the same topics. These topics were sales promotion, customer service, improving behavior and communication skills, techniques in selling, fashion and merchandise knowledge, visual merchandising, closing the sale, merchandise display techniques, improving the listening ability of salespersons, product and company information. They also provide leadership training and merchandising trainings to their sales personnel. The result of the study enabled the researcher to conclude that the ten apparel retail stores regardless of their store category are similar in the contents of their training program.